Explicit instruction in fitness exercise for PATHFit II (physical activities towards health and fitness) - Laarni Velez (Universitas Negeri Malang, 2023)
Explicit instruction is a purposeful way of overtly teaching students. Explicit in this case, means a clear-cut and finite method of teaching that includes both teaching and delivery procedures. Using this learning, the students perform the skills of the different fitness exercises through practical demonstration with clear and specific instruction. The teachers would tell the students using direct instructions to demonstrate the skills, respectively. Thus, this research determined the efficacy of explicit instruction in fitness exercises for pathfit II at Biliran Province State University – Main, Naval, Biliran during the academic year 2021 – 2022, as basis for enhancement activities. The study used a quasi-experimental research design and had one hundred (100) respondents involved in the survey. Findings revealed the skills performance of the students was excellent after using explicit instruction in fitness exercises as to; muscular strength – push up, muscular endurance - planking, flexibility – sit and reach, and cardiovascular endurance – 3-step test. In other words, there was a significant difference between how well students performed their skills before and after using explicit instruction in fitness exercises. In essence, this paper recommends adopting explicit instruction in teaching fitness exercise to enhance students’ skill performance in terms of muscular strength, muscular endurance, flexibility, and cardiovascular endurance to ensure that the students can adhere to the proper method of exercise to successfully complete the tasks.